2006
DOI: 10.1128/aem.03075-05
|View full text |Cite|
|
Sign up to set email alerts
|

Survival of Environmental Mycobacteria in Acanthamoeba polyphaga

Abstract: Free-living amoebae in water are hosts to many bacterial species living in such an environment. Such an association enables bacteria to select virulence factors and survive in adverse conditions. Waterborne mycobacteria (WBM) are important sources of community-and hospital-acquired outbreaks of nontuberculosis mycobacterial infections. However, the interactions between WBM and free-living amoebae in water have been demonstrated for only few Mycobacterium spp. We investigated the ability of a number (n ‫؍‬ 26) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 79 publications
8
122
1
1
Order By: Relevance
“…The 33 isolates corresponded to 5 mycobacterial species: M. fortuitum, M. conceptionense, M. chelonae, M. chimaera, and M. phocaicum (Table). Some of these mycobacteria already had been shown to survive in freeliving amebae and to be implicated in human diseases, such as M. chelonae (5). The same author demonstrated recently that 26 environmental mycobacteria survived in the trophozoites and cysts of Acanthamoeba polyphaga (5).…”
Section: Emerging Mycobacteria Spp In Cooling Towersmentioning
confidence: 93%
See 1 more Smart Citation
“…The 33 isolates corresponded to 5 mycobacterial species: M. fortuitum, M. conceptionense, M. chelonae, M. chimaera, and M. phocaicum (Table). Some of these mycobacteria already had been shown to survive in freeliving amebae and to be implicated in human diseases, such as M. chelonae (5). The same author demonstrated recently that 26 environmental mycobacteria survived in the trophozoites and cysts of Acanthamoeba polyphaga (5).…”
Section: Emerging Mycobacteria Spp In Cooling Towersmentioning
confidence: 93%
“…In 2003, cooling towers were reported to be a potential source of slow-growing mycobacterial species (1). Some mycobacterial species recently were shown to survive within amebae (5). We aimed to study the population of ameba-associated mycobacterial species in 3 cooling towers using a co-coculture method.…”
Section: Emerging Mycobacteria Spp In Cooling Towersmentioning
confidence: 99%
“…In addition, certain isolates of the soil-dwelling amoeba Dictyostelium discoideum persistently associate with bacteria, an association that has beneficial or detrimental outcomes depending on the environmental conditions (23)(24)(25). Amoebas can serve as environmental reservoirs for bacterial pathogens (26,27) or as training facilities for the adaptation of bacteria to evade eukaryotic phagocytosis or to survive intracellularly after phagocytosis (17,28). Although, for the eukaryotic host, some of these interactions may have decidedly unfortunate outcomes, such as the emergence of bacterial pathogenesis through intracellular adaptation, others may illuminate important evolutionary advances, such as the transition of bacterial endosymbionts into organelles that provide novel functionality.…”
Section: Significancementioning
confidence: 99%
“…It has also been reported that Mycobacterium spp. can enter and survive in the trophozoites and cysts of Acanthamoeba polyphaga (Adekambi et al, 2006). Therefore, investigation for eukaryotic communities is necessary to better understand the microbial ecology and potential health risk associated with pathogens in DWDSs.…”
Section: Introductionmentioning
confidence: 99%